Electrochemical behaviour and analysis of Zn and Zn–Ni alloy anti-corrosive coatings deposited from citrate baths. Issue 51 (14th August 2018) - Anwar, Shams; Zhang, Yahui; Khan, Faisal
Abstract : Anticorrosive coatings are a useful approach for protecting steel structures/machinery against corrosion. Abstract : Anticorrosive coatings are a useful approach for protecting steel structures/machinery against corrosion. Electrodepositions of zinc and zinc–nickel alloy films on steel substrates under various conditions from baths containing potassium citrate were studied. The effects of electroplating variables such as bath composition and current density on the coating composition, morphology, corrosion and mechanical properties were systematically investigated. The electrochemical and mechanical behaviour of Zn–Ni deposits obtained at 60 mA cm −2 from the citrate bath exhibited a lower corrosion current ( I corr ) and a less negative corrosion potential ( E corr ) compared to pure Zn and Zn–Ni alloy coatings from the non-citrate bath. The crystallite size of the Zn–Ni coating deposited from the citrate bath was 35.40 nm, and the Ni content of the coating was 8.3 wt%. The morphological properties and crystalline phase structure of the alloy coating were examined by scanning electron microscopy (SEM) and X-ray diffraction (XRD). The topographical structure of the coatings was analyzed by atomic force microscopy (AFM). The dominant γ-NiZn3 (815) and γ-Ni2 Zn11 (330) (631) plane orientations in the zinc–nickel alloy films improved the corrosion resistance. Zn–Ni films with smaller grain size and uniform coating had an increased impedance modulus and improved corrosion resistance.